Cu(I)/Cu(II) Creutz–Taube Mixed‐Valence 2D Coordination Polymers. Issue 1 (21st December 2022) - Li, Ning; Wu, Gang; Xi, Shibo; Wei, Fengxia; Lin, Ming; Qiu, Jinjun; Zheng, Jin‐Cheng; Yi, Jiabao; Seng, Debbie Hwee Leng; Lee, Coryl Jing Jun; Repaka, D. V. Maheswar; Liu, Xiaoming; et al.
Abstract: Graphene‐like 2D coordination polymers (GCPs) have been of central research interest in recent decades with significant impact in many fields. According to classical coordination chemistry, Cu(II) can adopt the dsp 2 hybridization to form square planar coordination geometry, but not Cu(I); this is why so far, there has been few 2D layered structures synthesized from Cu(I) precursors. Herein a pair of isostructural GCPs synthesized by the coordination of benzenehexathiol (BHT) ligands with Cu(I) and Cu(II) ions, respectively, is reported. Spectroscopic characterizations indicate that Cu(I) and Cu(II) coexist with a near 1:1 ratio in both GCPs but remain indistinguishable with a fractional oxidation state of +1.5 on average, making these two GCPs a unique pair of Creutz–Taube mixed‐valence 2D structures. Based on density functional theory calculations, an intramolecular pseudo ‐redox mechanism is further uncovered whereby the radicals on BHT ligands can oxidize Cu(I) or reduce Cu(II) ions upon coordination, thus producing isostructures with distinct electron configurations. For the first time, it is demonstrated that using Cu(I) or Cu(II), one can achieve 2D isostructures, indicating an unusual fact that a neutral periodic structure can host a different number of total electrons as ground states, which may open a new chapter for 2D materials. Abstract : A pair of isostructural Cu(I)/Cu(II) mixed‐valence Creutz–Taube 2D coordination polymers were synthesized using Cu(I) and Cu(II) precursors, respectively, which addressed a long‐standing controversy about metal ion oxidation states in 2D structures. More importantly, an unusual fact was unveiled that a neutral 2D coordination atomic structure can host a different number of total electrons as ground states without structural change.